Analisis E-Library Uinsa Kubuku sebagai Sarana Peningkatan Citra Perpustakaan - Hary Supriyatno (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
The trend of procuring e-libraries by libraries is motivated by the impact of the pandemic which has eliminated face-to-face services. The digital collection available in the e-library is a solution to meeting people's needs due to a shift in literacy culture from conventional to digital. Digital collections not only complement, but even replace print collections as a source of public information. Purpose Research. This study aims to determine the level of utilization of the Kubuku UINSA android based application and the image of the library as a result of its existence. Methods. The method used is the mixed method by maximizing observation and interview techniques in data acquisition. Results. The results of the study show that the utilization rate of the e-library is quite high. During the period June 2020 to April 2023, there were 31,545 visitors, 8,153 readers, 1,907 borrowers, and 26,531 copies of the collection used. Meanwhile, the image of the library is in the high category due to the existence of Kubuku UINSA. This can be seen from the four elements of the image, namely perception, cognition, motives, and attitudes which all show positive. the indicators are early introduction of applications through PBAK activities and knowledge of the types of collections available (perception). Reliability as a source of information because it consists of compulsory lecture books and the availability of digital collections as a substitute for printed books for course reading and reference (cognition). Small application size and easy access so there is no need to physically come to the library and new collections as needed (motive). Reading and citation of available collections for academic assignments as well as promotional behavior to others due to easy utilization and complete collections.Keywords: e-library, Kubuku UINSA, Library Image.